Marked mucosal lipid shifts in treatment refractory inflammatory bowel disease: a lipidomic study - Øystein K. Moe; Qian Gao; Dawei Geng; Einar Jensen; Rasmus Goll; Oddmund Nestegard; Mona D. Gundersen; Jon R. Florholmen; T. Moritz (BMC Gastroenterology)
Abstract Background Mechanisms causing non-response to biological agents in IBD remain to be fully understood. Thus, we aimed to characterize the lipid profile in treatment refractory non-immunogenic patients with adequate trough-levels. Methods Patients with IBD refractory to treatment with anti-tumour necrosis factor or vedolizumab were included from a Norwegian translation study. Mucosal lipid profiles were compared to reference groups. The reference groups included treatment naïve IBD patients with moderate to severe disease at debut who later achieved remission or response on antiTNFs, IBD patients treated to remission with biological agents, and healthy normal controls. Lipidomics analyses were performed on mucosal biopsies. Statistical analyses of lipid levels were carried out using generalized least squares. Lipidomics data were log2-transformed and auto-scaled before analysis. P-values were adjusted using Benjamini- Hochberg procedure to control the false discovery rate (FDR). Results Proinflammatory lipids including ceramides and sphingomyelins and protective lipids like glycerophosphocholines and glycerophosphoethanolamines were significantly decreased in treatment refractory UC patients compared to treatment naïve UC patients with moderate to severe disease. Compared to controls, major changes in ceramides (Cer), hexosyl ceramides (HexCer), sphingomyelins (SM), glycerophosphocholines (PC), glycerophosphoethanolamines (PE) and glycerophosphoserines (PS) were observed in treatment refractory UC patients. Refractory CD patients showed minor changes compared to the other CD-groups. There were no significant differences in the mucosal lipid levels of IBD patients in remission compared to normal controls. Conclusions The mucosal lipid profile of treatment refractory UC shows marked shifts compared to treatment naïve UC at debut with moderate to severe inflammation. These are novel findings which possibly indicate dynamic processes of long-standing mucosal inflammation. The mucosal lipid profile of IBD patients in remission seems to be similar to the normal state.